Analysis of long term trends of rainfall and temperature of Andit tid watershed, central highland of Ethiopia - DESALEGN, Ayele; GETACHEW, Tilahun; KASSA, Getacher (International Journal of Environmental, Sustainability, and Social Science, 2021)
The impacts of climate change and climate variability on human life led the scientific community to monitor the behavior of weather and climate variables. As a responsible body in the present study, trends and variations in climatic variables (i.e. rainfall, air temperature and soil temperature) were analyzed on monthly, seasonal (Belg, summer, spring and winter) and annual time scales for Andit tid watershed, central highland of Ethiopia. This was done using non-parametric statistical techniques, i.e. the Mann–Kendall (MK), over a period of 24 years. To detect the inhomogeneity of the data, autocorrelation has been taken into account using the Hamed and Rao method. The trend analysis revealed that monthly, seasonal and annual rainfall did show statistically insignificant decreasing trend at (P<0.05) level of significant. Annually, noticeable trend increase was found in maximum air temperature and noticeable decrease in minimum air temperature from the non-parametric statistical tests at a (P<0.05) level of significance. With this circumstance, the mean temperature showed insignificant increasing trend at (P<0.05). This type of analysis of several climatic variables at watershed level is helpful for the planning and management of water resources and the development of adaptation strategies in adverse climatic conditions.